Strategic and participatory design in integrated ventures. Fitness case La Plata, Argentina - Del Giorgio Solfa, Federico (Universidad de Boyacá, 2021)
The objective of this article is to analyze the relationships between theories of strategic design and participatory design, in multiple commercial alliances between local entrepreneurs from different sectors and their integrated application in the urban context. Various authors have dealt with these strategic issues in isolation and less frequently have addressed them from the entrepreneurial experience. A review of the specific literature allows us to account for the main concepts involved in this approach. The case being analyzed refers to a fitness-related venture in the city of La Plata, which articulated, together with other local actors, a collaborative strategy that led to the application of a superior business model for its sector. In addition, he capitalized on his role as an influencer on the social network Instagram, as a way to enhance the project's comprehensiveness. The topics that are addressed synthesize the key concepts that allow us to interpret the praxis relieved. And from them, create a model that can be applied in other markets and territories to promote young local development. And in this way, different actors, complementary products and services serve to jointly promote a co-productive and self-managed culture.